Peripheral immune markers and amyotrophic lateral sclerosis: a Mendelian randomization study - Hu, Zhengwei; Zuo, Chunyan; Mao, Chengyuan; Shi, Changhe; Xu, Yuming (Frontiers in Neuroscience, 2023)
The peripheral immune system changes in amyotrophic lateral sclerosis (ALS), but the causal relationship between the two is still controversial. In this study, we aimed to estimate the causal relationship between peripheral immune markers and ALS using a two-sample Mendelian randomization method. Genome-wide association study (GWAS) data on peripheral blood immune traits from European populations were used for exposure, and ALS summary statistics were used as the outcome. The causal relationship was evaluated by inverse variance weighting, MR-Egger, and weighted median methods and verified by multiple sensitivity analysis. We found that the increase of one standard deviation of lymphocyte count is related to reducing ALS risk. CD3 on effector memory CD4+ T cell, HLA DR+ CD4+ T cell, effector memory CD8+ T cell, terminally differentiated CD8+ T cell and CD28- CD8+ T cell is also a protective factor for ALS. Among the circulating immune protein, the increase of one standard deviation of α-2-macroglobulin receptor-associated protein (α-2-MRAP) and C4b showed associated with low risk of ALS, while Interleukin-21 (IL-21) increases the risk of ALS. Our study further reveals the important role of peripheral immune activity in ALS.